Reporting and case management of occupational exposures to blood-borne pathogens among healthcare workers in three healthcare facilities in Tanzania. Issue 4 (July 2016) - Lahuerta, Maria; Selenic, Dejana; Kassa, Getachew; Mwakitosha, Goodluck; Hokororo, Joseph; Ngonyani, Henock; Basavaraju, Sridhar V; Courtenay-Quirk, Cari; Liu, Yang; Kazaura, Koku; Simbeye, Daimon; Bock, Naomi; et al.
Background: In sub-Saharan Africa, blood-borne pathogens exposure (BPE) is a serious risk to healthcare workers (HCW). Methods: We conducted a cross-sectional study assessing BPE among HCW at three public hospitals in Tanzania. From August to November 2012, HCW were surveyed using Audio-Computer Assisted Self-Interview. All HCW at risk for BPE were invited to participate. Factors associated with reporting BPE were identified using logistic regression. Findings: Of the 1102 eligible HCW, 973 (88%) completed the survey. Of these, 690 (71%) were women and 499 (52%) were nurses and nurse assistants. Of the 357 HCW who had a BPE (32%) in the previous 6 months, 120 (34%) reported it. Among these 120 reported exposures, 93 (78%) HCWs reported within 2 h of exposure, 98 (82%) received pre- and post-HIV test counselling, and 70 (58%) were offered post-exposure prophylaxis (PEP). Independent factors associated with reporting BPE were being female (adjusted odds ratio [AOR], 2.0; 95% confidence interval [CI], 1.2–3.5), having ever-received BPE training (AOR, 2.0; 95% CI, 1.2–3.5), knowledge that HCW receive PEP at another facility (AOR, 2.6; 95% CI, 1.5–4.4), low/no perceived risk related to BPE (AOR, 4.2; 95% CI, 1.9–9.4) and HIV testing within the past year (AOR, 2.3; 95% CI, 1.2–4.4). Conclusion: These results highlight the importance of appropriate training on the prevention and reporting of occupational exposure to increase acceptance of HIV testing and improve access to PEP after BPE.